Mechanical properties and in vitro evaluation of thermoplastic polyurethane and polylactic acid blend for fabrication of 3D filaments for tracheal tissue engineering - Abdul Samat, Asmak; Yahaya, Badrul Hisham; Abdul Hamid, Zuratul Ain; Jaafar, Mariatti (MDPI, 2021)
Surgical reconstruction of extensive tracheal lesions is challenging. It requires a mechanically stable, biocompatible, and nontoxic material that gradually degrades. One of the possible solutions for overcoming the limitations of tracheal transplantation is a three-dimensional (3D) printed tracheal scaffold made of polymers. Polymer blending is one of the methods used to produce material for a trachea scaffold with tailored characteristics. The purpose of this study is to evaluate the mechanical and in vitro properties of a thermoplastic polyurethane (TPU) and polylactic acid (PLA) blend as a potential material for 3D printed tracheal scaffolds. Both materials were meltblended using a single screw extruder. The morphologies (as well as the mechanical and thermal characteristics) were determined via scanning electron microscopy (SEM), Fourier Transform Infrared (FTIR) spectroscopy, tensile test, and Differential Scanning calorimetry (DSC). The samples were also evaluated for their water absorption, in vitro biodegradability, and biocompatibility. It is demonstrated that, despite being not miscible, TPU and PLA are biocompatible, and their promising properties are suitable for future applications in tracheal tissue engineering.